Study on strength of fiber reinforced clayey sand - Chegenizadeh, Amin; Nikraz, Hamid (Research Publishing Services, 2011)
Composite soils have been widely used in civil engineering applications, especially in slopes, embankment dam and landfills. This paper aims to investigate effect of fiber inclusion on Unconfined Compressive Strength of composite soil (i.e. sand composite). A series of laboratory Unconfined Compression tests carried out to evaluate fiber effect on strength behavior of composite sand. Clayey sand was selected as soil part of the composite and natural fiber was used as reinforcement to enhance the strength. The fiber parameters changed from one test to another, as fiber length were changed from 10 mm to 30 mm and fiber content were selected as 1% and 4%. For each test, stress_strain graph derived and the results were compared. The results proved that inclusion of fiber affected strength behaviour of sand composite so that increasing in fiber content and length caused increasing in Unconfined Compressive Strength (UCS).